KUR'AN'A GÖRE ÇOCUKLAR ARASINDA CiNSiYET AYRlMCillGI -Kız Çocuklarına Karşı Tutumlar- - Kasapoğlu, Abdurrahman (Fırat University, 2005)
In many societies, tlıere were gender discrimination tlırouglıout history. This arause positive conditions for sons and negative conditions for dauglıters. Quran explains that dauglıters are as valuable as sons are. ı'vforeover, it says that dauglıters should benefit from and use equally all riglıts as sons do, especially for educati01ı riglıts. İt tries to awaken the concience about abolis/ıing tlıe negative judgement against dauglıters.
Keywords: Religious Studies; Din Araştırmaları